KADAR KORELASI HEMOGLOBIN, FERITIN SERUM DAN SATURASI TRANSFERIN IBU HAMIL TRIMESTER III DENGAN BERAT BADAN LAHIR BAYI DI RS PKU MUHAMMADIYAH BANTUL YOGYAKARTA - , SARASTITI ALIFANINGDYAH; , dr.Tri Ratnaningsih, M.Kes, Sp.PK (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Iron deficiency anemia (ADB) is a type of malnutrition with the highest prevalence in the world. Prevalence of ADB in Indonesia is still very high, 44.5 %. The largest population of people with anemia are pregnant women. ADB complication in pregnant women which is common and has a poor prognosis for the baby is Low Birth Weight. Objective: To study the correlation of the hemoglobin and iron status of third trimester pregnant women with infantâs birth weight in PKU Muhammadiyah Hospital Bantul, Yogyakarta Methods : The study is a type of cross sectional using primary data, ie data from laboratory tests of blood veins from third trimester pregnant women and infant birth weight data. Examination of the samples was conducted in the Parahita Laboratory and the Laboratory of Clinical Pathology Hospital Dr. Sardjito, Yogyakarta. Inclusion criteria include all mothers who gave birth in PKU Muhammadiyah Hospital, Bantul between the months of May to December 2013 Results: The total of subjects studied are 220 pregnant women, with the data of hemoglobin, serum ferritin, transferrin saturation and birth weight infants in each subject. Statistical analysis showed no significant correlation (p > 0.05) between birth weight infants with three independent variables, namely hemoglobin (p: 0.914), ferritin (p: 0.761), and transferrin saturation (p: 0.904) in third trimester pregnant women. Conclusion : There is no correlation between hemoglobin level, serum ferritin and transferrin saturation in the third trimester pregnant women with infantâs birth weight in the PKU Muhammadiyah Hospital, Bantul Yogyakarta.